Learning To Promote Students’ Mathematical Curiosity And Creativity - Rahayuningsih, Sri (2023)
[Background] Discovery learning is a model that guides students to actively learn in finding concepts or knowledge through an inquiry process based on the data or information obtained from experiments or observations. [Objective] The present study examined the implementation of a modification of discovery learning using mind mapping in promoting students’ mathematical curiosity and creativity. [Method] A Classroom Action Research (CAR) design was employed in this study. The participants were 250 students in Middle Indonesian who registered in the academic year of 2020/2021. [Results] The descriptive analysis showed that the students achieved an average score of 44.04 with a standard deviation of 18.716 in pre-CAR, 52.48 with a standard deviation of 22.978 after cycle I, and 76.72 with a standard deviation of 17.097 after cycle II. Based on the students’ mathematical creative thinking scores, 2 (8%) students could perform creative thinking in pre-CAR, 6 (24%) students after cycle I, and 22 (88%) students after cycle II. These figures indicated that the students classically achieved the ability to think creatively in mathematics after cycle II. [Conclusion] It was concluded that the implementation of modified discovery learning and mind mapping could promote students’ mathematical creative thinking ability. The interview results also suggest that the learning model could increase mathematical curiosity of both the low and high achievers.